RESIN EXTRACTION FROM NYAMPLUNG SEED OIL - Griffine Oliviery, Yehezkiel
Seeds from nyamplung that are widespread in Indonesia have a great potential to be used as biodiesel. In the process of producing oil from nyamplung seeds, there is a by-product called resin with high concentration that can reduce the performance of biodiesel. Meanwhile, this resin contains phenolic compounds that are beneficial for pharmaceutical and cosmetic purposes. Therefore, a further study about taking resin from nyamplung seed oil is needed to improve biodiesel performance and to utilize resin. The purpose of this study is to determine the distribution of nyamplung seed oil, determine the effect of solvent ratio temperature on the yield and composition in both solvent fraction, and determine the optimum condition of the variation carried. The composition of nyamplung seed oil used is obtained from the literature. Variations made include the ratio of the solvent and temperature. There are five general stages in this study including simulation building, feed validation, simulation validation, liquid-liquid extraction simulation, and simulation results analysis. Extraction is carried out by the simulation using n-hexane-ethanol solvent by ratio of 0.05:1 until 20:1 and temperature 30oC until 80oC. This simulation results distribution of triglycerides, abietic acid, and FFA that increase as the solvent ratio increases by 88% – 99%, 12% – 98%, dan 8% – 98%, respectively. As the solvent ratio increases, bulk oil yield increase by 58.67% – 99.86% and bulk resin yield decrease by 41.33% – 0.14%. In addition, as the solvent ratio increases, triglycerides concentration in hexane and ethanol decrease by 958 mg/g – 700 mg/g and 341 mg/g – 24 mg/g respectively, while abietic acid concentration in hexane and ethanol increase by 3.51 mg/g – 20 mg/g and 42.91 mg/g – 57 mg/g, respectively. The optimum condition of extraction is carried out with 0.05 solvent ratio and 30oC.